PENGARUH RISIKO KREDIT, RISIKO LIKUIDITAS DAN RISIKO SOLVABILITAS TERHADAP PROFITABILITAS BANK (STUDI PADA BANK PERSERO YANG BEROPERASI DI INDONESIA) - Azwansyah `Habibie (JURNAL MUTIARA AKUNTANSI, 2017)
This study aims to determine the effect. Against the level of bank profitability. This research is conducted with quantitative approach by using secondary data that is quarterly financial report of publication of state bank in question to Bank Indonesia. The population and sample are 64 quarterly financial reports of bank publications consisting of 4 banks and study period from 2011 to 2014. The results of this study indicate the existence of credit risk, liquidity risk and risk are partially insignificant to the profitability of state banks but simultaneous credit risk, liquidity risk and solvability risk significantly to the profitability of state-owned banksKeywords: Credit Risk, Liquidity Risk, Solvency Risk, Bank Profitability